Nasal CPAP Improves the Quality of Life and Lessens the Depressive Symptoms in Patients with Obstructive Sleep Apnea Syndrome - AKASHIBA, Tsuneto; AKAHOSHI, Toshiki; KAWAHARA, Seiji; HORIE, Takashi (Internal Medicine, 2005)
Objective To assess changes in response to nasal continuous positive airway pressure (CPAP) in patients with obstructive sleep apnea syndrome (OSAS) concerning excessive daytime sleepiness (EDS), depressive state, and quality of life (QOL). Patients and Methods We assessed for EDS using the Epworth sleepiness scale (ESS), for mood using The Zung self-depression scale (SDS), and for QOL using Short-Form 36 (SF-36) in 132 patients with obstructive sleep apnea syndrome (OSAS) and control subjects. Patients had severe OSAS (apnea-hypopnea index, 59.4±23.8/h) and were more hypersomnolent and depressed, and had poorer QOL than 38 age- and gender-matched controls. Results Before treatment most QOL domains in the SF-36 were significantly associated with patients’ SDS scores. With nasal CPAP, ESS and SDS scores were respectively decreased from 9.7±4.5 to 4.0±2.4 (p<0.0001) and from 49.2±10.4 to 45.1±9.6 (p<0.0005). Total SF-36 score and scores for seven of eight domains were increased significantly with treatment. Thus, nasal CPAP lessens EDS and depression, and improves QOL, in patients with severe OSAS. Further, magnitudes of changes in total SF-36 scores and in five of eight domains correlated significantly with magnitude of change in SDS score upon nasal CPAP treatment. No relationship was evident between treatment-associated score changes in SF-36 domains and ESS score change. Conclusion Although patients with severe OSAS have poorer QOL than control subjects, nasal CPAP appears to improve QOL by alleviating depression.